Concurrent validity of countermovement and squat jump height assessed with a contact mat and force platform in professional soccer players - Ruf, L.; Altmann, S.; Müller, K.; Rehborn, A.; Schindler, F.; Woll, A.; Härtel, S. (Frontiers in Sports and Active Living, 2024)
Purpose: The aim of this study was to assess the concurrent validity of a contact mat against force plates to measure jump height in countermovement jump (CMJ) and squat jump (SJ) in professional soccer players.